IRON OVERLOAD, COMPROMISED SALIVARY FUNCTION, AND DENTAL CARIES RISK IN BETA-THALASSEMIA MAJOR: A CROSS-SECTIONAL - Ramadhani, Amilia; Pramuditya, Hafizh Zufar; Nurcahyani, Putri Silvia; Taqwim, Ali; Basalamah, Muhammad; Widodo, A. Haris Budi; Rujito, Lantip (Universitas Muhammadiyah Semarang, 2025)
Background: β-thalassemia major patients exhibit higher dental caries prevalence due to systemic complications including iron overload from regular blood transfusions. This study aimed to assess dental caries status, salivary pH, and buffer capacity in β-thalassemia major patients and investigate correlations with ferritin blood concentration.Method: A cross-sectional analytical study was conducted on 24 β-thalassemia major patients aged 12-17 years. Salivary function was assessed by salivary pH and buffer capacity. Dental caries status was evaluated using the DMF-T index. Ferritin blood concentrations were correlated with salivary function and dental caries using Pearson analysis.Outcome: Mean salivary pH was 5.74±0.63 (acidic), buffer capacity was 3.98±0.21, DMF-T score was 6.17±1.97, and ferritin level was 5830.54±2823.91 ng/mL. Ferritin levels showed moderate negative correlations with salivary pH (r=-0.718, p<0.001) and buffer capacity (r=-0.737, p<0.001), and positive correlation with DMF-T scores (r=0.696, p<0.001). Strong negative correlations were found between DMF-T scores and salivary pH (r=-0.915, p<0.001) and buffer capacity (r=-0.913, p<0.001).Conclusion: Iron overload significantly compromises salivary parameters, creating an acidogenic oral environment that promotes dental caries development in β-thalassemia major patients, emphasizing the need for integrated oral health monitoring in thalassemia management protocols.